Sociological Study on the Impacts of Heatwaves on Exclusive Breastfeeding Among Nursing Mothers in North Eastern Nigeria - Hussaini Ibn Mohammed (INTERNATIONAL JOURNAL OF MEDICAL EVALUATION AND PHYSICAL REPORT, 2026)
Sub-Saharan Africa faces growing risks to maternal and child health from heatwaves, exacerbated by climate change. In places like North-Eastern Nigeria, with high temperatures and inadequate health services, environmental and socio-cultural factors can influence optimal infant feeding by nursing mothers. This research explores the sociological effects of heatwaves on exclusive breastfeeding (EBF) for nursing mothers in North-Eastern Nigeria. The study used a descriptive cross-sectional survey design with nursing mothers who visited primary health care clinics. The study used structured questionnaires to elicit information on knowledge, attitudes and practices of breastfeeding during periods of high heat. Data were analysed using descriptive and inferential statistics. Results suggest that breastfeeding practices are strongly affected by heatwaves through behavioural and socio-cultural pathways. Many mothers reported supplementing with water or other feedings during hot weather due to infant dehydration. Research indicates that exposure to heat decreases the frequency of breastfeeding due to discomfort, fatigue and increased physical demands. Parents' cultural beliefs and family pressure were found to play an important role in feeding choices. The study's results are consistent with other research in sub-Saharan Africa that shows elevated ambient temperature affects infant feeding and maternal care. This research calls for climate-responsive maternal health strategies, including educational interventions to counter myths on infant dehydration and increased support for breastfeeding mothers during heatwaves. Enhancing community health education and incorporating climate change considerations into maternal health interventions are essential to promote exclusive breastfeeding in North-Eastern Nigeria.